PENERAPAN METODE ACTIVITY BASED COSTING (ABC) SYSTEM DALAM PENENTUAN HARGA POKOK PRODUKSI - Syarifudin, Akhmad (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
The purpose of this study was to determine the calculation of the cost of production by using the activity based costing method and knowing the comparison of the results of the calculation of cost of goods manufactured based on the activity based costing method with the cost of production at UD Mitra Sejahtera.The use of the ABC system in the distribution of costs is more appropriate than the conventional system applied to UD Mitra Sejahtera Plastindo, because in the ABC system overhead costs on each product are charged to two driver costs, namely the number of kwh and the amount of production according to the activities carried out in plastic manufacturing, namely cutting and packaging, while the conventional system imposes product overhead costs on one driver cost, namely the amount of production. Calculation of Cost of Production (HPP) with ABC system and conventional system applied to UD Mitra Sejahtera Plastindo shows that the calculation of HPP causes distortion (difference), namely overcost for plastic products of PE,, kg, ½ kg, 1 kg, 2 kg and 2½ kg. The occurrence of this distortion causes inaccurate cost reporting, thus affecting the selling price.